2002
DOI: 10.1093/jjco/hyf061
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Stomach Cancer in Brazil (II): a Case-control Study among Japanese Brazilians in Sao Paulo

Abstract: The introduction of the habit of daily beef consumption among Japanese immigrants and their descendants may be associated with stomach cancer risk. The protective effect of fruit consumption was confirmed in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 0 publications
0
74
1
6
Order By: Relevance
“…Of these 17 studies, 8 were population-based case-control studies [12,13,18-20,22,25,26], 7 were hospital-based case-control studies [14-17,21,23,24], and 2 were cohort studies [27,28]. …”
Section: Resultsmentioning
confidence: 99%
“…Of these 17 studies, 8 were population-based case-control studies [12,13,18-20,22,25,26], 7 were hospital-based case-control studies [14-17,21,23,24], and 2 were cohort studies [27,28]. …”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in Japan (17) reported data from 2 regions, one affected by atomic bomb and one not affected; only the results from the latter were considered in our analysis. Two studies reported the results separately using different groups of controls: population-and hospital-based controls (22), or including and excluding volunteers (35). In these instances, we only considered results in which population-based controls were considered and volunteers were excluded.…”
Section: Data Extraction and Statistical Analysismentioning
confidence: 99%
“…Of the 12 studies, only two 2,15 had been carried out in other locations with high concentrations of Japanese descendants. Table 1 shows the list of the articles and the characteristics of each study.…”
Section: Studies With Japanese-braziliansmentioning
confidence: 99%
“…With regards to language, eight articles [7][8][9]15,26,[32][33][34] were in English and four 1,5,37,48 in Portuguese. As for the study design used, two studies were cohort studies 4,26 and the others [1][2][3]5,[7][8][9]15,37,48 were cross-sectional studies, with three 1,2,5 being comparisons of transversal data.…”
Section: Studies With Japanese-braziliansmentioning
confidence: 99%
See 1 more Smart Citation